Asuhan Keperawatan Pada Pasien Diabetes Mellitus Tipe II Dengan Pemberian Intervensi Terapi Relaksasi Otot Progresif Terhadap Penurunan Kadar Glukosa Darah Di Ruang Cempaka RSUD Kabupaten Tangerang - Novita Sariayu Sitompul; Meynur Rohmah; Dwi Wahyuni (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Type 2 diabetes mellitus is a metabolic disorder characterized by an increase in blood sugar due to decreased insulin secretion by pancreatic beta cells or insulin resistance. Difficulty controlling blood sugar levels is a problem experienced by every person with type 2 diabetes mellitus. Several reasons cause uncontrolled blood sugar levels, such as the patient not wanting to exercise, poor diet and negligence in treatment. Management of diabetes mellitus can be done with non-pharmacological therapy in the form of physical exercise. Physical activity will make the body's metabolism work more optimally which will result in blood glucose levels being controlled so that holistic treatment is needed. One of the non-pharmacological physical exercise therapies that can be given to diabetes mellitus sufferers is progressive muscle relaxation techniques. Research method: Implementing Progressive Muscle Relaxation Therapy in Type II Diabetes Mellitus patients to reduce Blood Glucose Levels. Research results: The results of implementation and evaluation for 3 days with Progressive Muscle Relaxation Therapy intervention showed objective and subjective changes in Type II Diabetes Mellitus patients as well as changes in blood glucose levels before and after being given Progressive Muscle Relaxation Therapy. Conclusion: There is a decrease in Blood Glucose Levels after Progressive Muscle Relaxation Therapy.